A life-threatening complication of undiagnosed congenital idiopathic megacolon. (26th August 2010) - Kabeer, Syed; Dvorkin, Lee; Carrannante, James; Linehan, Ian
Abstract : A case of undiagnosed congenital idiopathic megacolon in a 16-year-old boy who presented with toxic megacolon and cardiovascular instability with a background of longstanding constipation is presented. He underwent life-saving subtotal colectomy from which he made a full recovery.